Brief Mindfulness Practice Course for Healthcare Providers. (July 2021) - Seidel, Laurie Walker; Dane, Francis C.; Carter, Kimberly Ferren
Abstract : OBJECTIVE: The aim of this study was to examine the short-term and sustained effect on well-being, burnout, and mindful awareness of an abbreviated mindfulness practice course designed for nurses and other healthcare professionals. BACKGROUND: Most mindfulness programs are impractical for frontline healthcare providers because of the intensive, off-site initial training and prolonged practice commitment. A psychiatric nurse educator developed a brief training program tailored for healthcare providers. METHODS: Two institutional review board–approved studies examined the abbreviated mindfulness practice course for healthcare providers: the first, a single-group pretest-posttest design with 25 nursing employees in an academic medical center, and the second, a randomized controlled trial with 83 healthcare professionals. RESULTS: Significant improvement in mindful awareness and at least 1 indicator of burnout were demonstrated. Improvements in quality of life were noted with nurses. CONCLUSIONS: Findings support the short-term and sustained impact of this brief mindfulness curriculum on mindful awareness, quality of life, and aspects of burnout for healthcare professionals. Abstract : Supplemental digital content is available in the text.